CaMKII in Regulation of Cell Death During Myocardial Reperfusion Injury - Yang, Yingjie; Jiang, Kai; Liu, Xu; Qin, Mu; Xiang, Yaozu (Frontiers in Molecular Biosciences, 2021)
Cardiovascular disease is the leading cause of death worldwide. In spite of the mature treatments of myocardial ischemia（MI）, post-MI reperfusion injury results in high morbidity and mortality. Cardiomyocyte Ca2+ overload is a major factor of I/R injury, initiating a cascade of events contributing to cardiomyocyte death and myocardial dysfunction. Ca2+/calmodulin-dependent protein kinase II (CaMKII) plays a critical role in cardiomyocyte death response to I/R injury, whose activation is a key feature of myocardial I/R in causing intracellular mitochondrial swelling, endoplasmic reticulum（ER）Ca2+ leakage, abnormal myofilament contraction and other adverse reactions. CaMKII is a multifunctional serine/threonine protein kinase, and CaMKIIδ, the dominant subtype in heart, has been widely studied in the activation, location, related pathways of cardiomyocytes，which has been considered as a potential targets for pharmacological inhibition, while most attempts failed in clinical trials. In this review, we summarize a brief overview of CaMKII various post-translational modifications and its properties in myocardial I/R injury. We focus on the molecular mechanism of CaMKII involved in regulation of cell death induced by myocardial I/R including necroptosis and pyroptosis of cardiomyocyte. We highlight that targeting CaMKII modifications and cell death involved pathways may provide new insights to understand the conversion of cardiomyocyte fate in the setting of myocardial I/R injury.